Design and Build Features Chat on Renting Book Application Based Web Technology - Rizky Maulana Fanani; Irwan A Kautsar (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This research is motivated by the development of innovation in the field of technology from time to time. The existence of a book rental application makes it easy for users to carry out book rental activities, users need communication so that rental activities can run well. Communication is needed to exchange messages between message senders and message recipients, chat features are needed in book rental applications. The addition of the chat feature to the book rental application is needed so that communication between tenants and landlords can be easily carried out and run well. By using the PHP programming language and mySql database to organize, store, and manage the data needed in application design, it is hoped that it can be developed by developers easily so that applications can run on mobile devices so that applications can be used on all devices. This study uses the literature study method and also from the author's observations on chat applications that currently exist. In its implementation, this feature works well and efficiently, the result is that users can communicate between users in the book rental application